DINÂMICA DA PAISAGEM E PERCEPÇÃO AMBIENTAL: uma análise do assentamento São Manoel, Anastácio-MS - POLYANA MILENA SIMAO (2021)
The research deals with the rural landscape, with a study of the São Manoel Settlement, located in the municipality of Anastácio, Midwest of the state of Mato Grosso do Sul. It aims to analyze the dynamics of the landscape and the environmental perception of the residents of the São Manoel Settlement, focusing, in addition to the physical characteristics, on the historical and socioeconomic aspects for the analysis of the residents' perception of the landscape and their affective link with the place. The theoretical-methodological contribution adopts the humanistic geography line, which contemplates the evolution of geographic studies on landscape and environmental perception. As a methodological procedure, the research was developed through a quanti-qualitative approach, with the application of semi-structured interviews directed at the residents and field data survey, in addition to the use of data from governmental and nongovernmental agencies, as well as secondary data from research already developed in the area. The results sought to contribute with data and reflections arising from the perception of the settlers, considering the need to look at sustainability, based on an analysis that considers their history, productivity and the existence of an affective link with this environment. It was found that, according to the socio-economic conditions, the initial predominant production was farming in most of the settlement, and currently the economic development occurs through individual productions, with the cultivation of pasture for dairy cattle and beef cattle, followed by farming on a smaller scale. Through the knowledge of the natural and biotic physical aspects, it was elucidated that the dynamics of the landscape in the São Manoel settlement has been altered according to the actions exercised by the residents over the course of twenty-eight years and that they perceive the influence of this interrelationship awakening feelings of hope for improving the quality of life in general, highlighting the affective link with their place, which is the São Manoel settlement.